Pasta Production: Complexity in Defining Processing Conditions for Reference Trials and Quality Assessment Methods. Issue 5 (18th July 2017) - Murray, Jessica C.; Kiszonas, Alecia M.; Morris, Craig F.
Abstract : Pasta is a simple food made from water and durum wheat ( Triticum turgidum subsp. durum ) semolina. As pasta increased in popularity, studies endeavored to analyze the attributes that contribute to high‐quality pasta. Despite being a simple food, the laboratory‐scale analysis of pasta quality is a complex process. Spaghetti is the most commonly studied form of pasta because its long, uniform shape lends itself well to analysis. Pasta production at a laboratory scale is not standardized, leading to large amounts of variation owing to differing equipment and protocols. Pasta production protocols vary in their target moisture content, mixing profile, extrusion die material, and spaghetti diameter. Once pasta is extruded, the equipment and protocols used to dry the pasta at the laboratory scale are far from consistent. Measurement of pasta quality parameters is also lacking in updated standardized methods, making it difficult to compare pasta quality data among laboratories. AACC International is actively working to develop an improved method for laboratory‐scale pasta production and analysis via the Pasta Products Analysis Committee. This review summarizes the equipment, protocols, and methods utilized in pasta quality studies.